"the blind leading the blind" (The Biblical archaeology review, 2021)
The phrase is a metaphor used to describe a situation when uninformed people are being advised or led by others who appear to be inept. Usually, it carries a connotation of harm and misfortune inflicted on the inexperienced by their misguided superiors. Although the saying was widely used in antiquity, it does not conform […]